PREDICTION OF THE USE OF REFRIGERANTS IN LOW-TEMPERATURE EQUIPMENT - J. V. Tatarenko; V. M. Mizin; N. O. Rachkovskiy (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives Determination of prospects for the use of various refrigerants, as well as the potential for their interchangeability in low-temperature equipment in accordance with the conditions of the Kigali Amendment to the Montreal Protocol on substances that deplete the ozone layer.Method A computer simulation of heat exchange processes based on generally accepted dependencies was carried out and data for the construction of refrigeration machine elements obtained.Results R717 and R410A are recommended for use in medium- and low-temperature machines. R32 refrigerant is used in high-temperature refrigeration machines, especially in units with finned copper tubes. The low vapour content of R32 refrigerant prevents steaming of the upper layers of the tube bundle, leading to an increase in the level of the refrigerant in the evaporator and in the working area of the evaporator tube bundle. For R32, it is necessary to conduct additional research to find an alternative refrigerant. The highest values of the heat transfer coefficient are obtained when working on refrigerants R410A and R717.Conclusion The implemented algorithms can be helpful for obtaining the characteristics of the steam-compressor refrigerator elements across a wide range of boiling and condensing temperatures taking various factors and the percentage composition of the mixed working substance into account. This is a highly important consideration when converting the machines to run on alternative refrigerants.